Diagnosis of pre professional practices: case school of Industrial Engineering UNMSM - León Velásquez, William (2011)
The aim of this paper is to measure the practitioner Academic Professional School of Industrial Engineering at San Marcos University that conducts its business practices in the public or private., Satisfaction, job expectations, integration, working relationship with your boss and colleagues work. Also been measured on the perception of firms regarding the performance of the practitioner through the variables: satisfaction, skills and knowledge, organized labor, problem identification and response to and communication with their superiors. Prepared two types of surveys: one aimed at students who are doing their training and one to the immediate superior. The surveys were considered indicators of perception and satisfaction needed for this type of research. In this research we worked with a sample of 39 companies in the period of 2010 and reached the following results: • The student has a good degree of satisfaction with their pre-professional. • The company perceives a high degree of acceptance regarding the performance of the practitioner. • There is difficulty in communication between the leader and practitioner, 42.55% feel that their level of skill is average, only 8.51% feel that good.